Missed Torsion of an Undescended Intra-Abdominal Testis Presenting as Acute Abdomen in an Adult: A Preventable Loss (Journal of Surgical Sciences, 2026)
We report a case of a 22-year-old man with a lifelong uncorrected left intra-abdominal undescended testis presented with sudden severe left lower abdominal pain and vomiting. The initial evaluation at another hospital failed to recognize the absent testis and to perform a scrotal examination; he was treated for suspected intestinal obstruction. On transfer, physical examination revealed a small, empty left hemiscrotum and an impalpable left testis. Urgent color Doppler ultrasound of the left inguinal region showed a 3.1×2.8 cm left testis at the internal inguinal ring with heterogeneous echotexture and absent intratesticular blood flow. The findings were consistent with torsion of the undescended testis The patient underwent immediate laparoscopic exploration, left orchidectomy was performed. Histopathology confirmed hemorrhagic infarction and a congested epididymis; no malignancy was found. Serum tumor markers (AFP,b-hCG, LDH) were normal. This case highlights that undescended testicular torsion can present as an acute abdomen and be easily missed in adults. We emphasize the importance of routine genitourinary examination in young males with abdominal pain, the benefits of early orchiopexy for cryptorchidism, and the need for contralateral testis fixation to prevent future torsion.Journal of Surgical Sciences 2023;27(1): 23-27